Additive Manufacturing and Characterization of René 80 Superalloy Processed Through Scanning Laser Epitaxy for Turbine Engine Hot‐Section Component Repair1. Issue 7 (15th May 2015) - Acharya, Ranadip; Bansal, Rohan; Gambone, Justin J.; Kaplan, Max A.; Fuchs, Gerhard E.; Rudawski, N. G.; Das, Suman
<x xml:space="preserve">Abstract</x> This article demonstrates single‐pass fabrication of thick, crack‐free deposits of René 80, a high gamma‐prime "non‐weldable" superalloy, atop like‐chemistry substrates through scanning laser epitaxy (SLE), a metal powder bed‐based laser additive manufacturing (AM) technique. Microstructural investigations and processing zone identification are presented. Optical microscopy and scanning electron microscopy reveal the segregated dendritic microstructure with the presence of finer carbides and primary γ′ particles. Transmission electron microscopy reveals a bimodal distribution of finer secondary γ′ particles in the deposit region. Microindentation hardness measurements show an increase in the hardness value by 25% in the deposit region compared to the cast substrate due to microstructural refinement. In addition to the achievement of metallurgical continuity across the interface and improved hardness in the deposit, the crack‐free deposits obtained here for René 80 represent one of the few successes reported for a non‐weldable alloy of its kind. The results presented here illustrate the significant potential of SLE for the AM‐based repair of existing and AM‐based construction of entirely new gas turbine hot‐section components utilizing powders of high γ′ nickel‐based superalloys that have long been known to have high tendency for cracking under the processing conditions associated with traditional welding, joining, and cladding approaches.